Magnitude of Construction Cost and Schedule Overruns in Public Work Projects. (18th December 2013) - Shrestha, Pramen P.; Burns, Leslie A.; Shields, David R.
Abstract : This study analyzed 363 Clark County Department of Public Works (CCDPW) projects to determine construction cost and schedule overruns in various types and sizes of the projects. The sample projects were constructed from 1991 to 2008, with a total construction cost of 1.85 billion, equivalent to 2012 cost. A one-factor ANOVA test was conducted to determine whether construction cost and schedule overruns significantly varied based on types and sizes of the projects. The study showed that large, long-duration projects had significantly higher cost and schedule overruns than smaller, short-duration projects.